2005
DOI: 10.1158/0008-5472.can-05-0300
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Proapoptotic Antiganglioside GM2 Monoclonal Antibody and Evaluation of Its Therapeutic Effect on Melanoma and Small Cell Lung Carcinoma Xenografts

Abstract: Monoclonal antibodies have begun to show great clinical promise for the treatment of cancer. Antibodies that can directly affect a tumor cell's growth and/or survival are of particular interest for immunotherapy. Previously, we described monoclonal antibody DMF10.62.3 that had antiproliferative and proapoptotic effects when it bound an antigen of unknown identity on tumor cells in vitro. In this report, we determined that DMF10.62.3 and a clonally related antibody DMF10.167.4 recognize the ganglioside GM2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…However, the possible activation of these signaling processes by anti-ganglioside mAbs is still unknown. There are only evidences of apoptosis induction in melanoma and small cell lung cancer cells by anti-GM2 and anti-GD2 antibodies, respectively (15,16). In the present report, we described for the first time that an anti-NGcGM3 antibody induced a novel cell death mechanism.…”
Section: Introductionsupporting
confidence: 46%
“…However, the possible activation of these signaling processes by anti-ganglioside mAbs is still unknown. There are only evidences of apoptosis induction in melanoma and small cell lung cancer cells by anti-GM2 and anti-GD2 antibodies, respectively (15,16). In the present report, we described for the first time that an anti-NGcGM3 antibody induced a novel cell death mechanism.…”
Section: Introductionsupporting
confidence: 46%
“…Indeed, mAbs with specificity for GM2 bind epitopes on a large number of tumor lines, but do not recognize normal primary lines or most normal tissues (24). These Abs have been shown to mediate both complement-dependent cytotoxicity and Ab-dependent cellular cytotoxicity (53), which variously block the proliferation of some tumor cells in vitro, inhibit the outgrowth of micrometastases (54), and/or prevent the establishment of murine tumors in vivo (24,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mAbs with specificity for GM2 bind epitopes on a large number of tumor lines, but do not recognize normal primary lines or most normal tissues (24). These Abs have been shown to mediate both complement-dependent cytotoxicity and Ab-dependent cellular cytotoxicity (53), which variously block the proliferation of some tumor cells in vitro, inhibit the outgrowth of micrometastases (54), and/or prevent the establishment of murine tumors in vivo (24,55,56). Mixed results, however, have been reported for related human trials, as follows: whereas anti-GM2 mAbs have been found to successfully eradicate melanoma metastases (57), in some cases anti-murine Ab responses are induced that interfere with and inhibit efficacy of the treatment (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hamster monoclonal anti-GM2 antibody (DMF10.167.4) was a gift from Corixa Corp. (Seattle, WA) and Dr. Kenneth Rock (Department of Pathology, University of Massachusetts Medical School, Worcester, MA; ref. 27). Ficoll-Hypaque was purchased from Amersham Pharmacia Biotech AB (Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%